Factors Influencing the Phenomenon of Political Coup: A Comparative Study in the History of Russian Coups - Al-Mekaimi, Haila Hamad (Dirasat: Human and Social Sciences, 2024)
Objectives: This research aims to study the influencing factors in the phenomenon of Russian coups throughout Russian history, with the goal of projecting the future of the contemporary Russian political system in terms of stability or change. Methods: The research adopts the structural approach by focusing on the political, economic, social, and external factors that cause the phenomenon of coups. The research also relied on the comparative historical method to compare the most important factors affecting the phenomenon of coups in Russian history. The research was also the result of a field study conducted by the researcher at Bishkek State University in the Faculty of Oriental Sciences and International Relations in the Kyrgyz Republic during the period 1-20 August 2023. It included holding a workshop with a number of specialists in Russian history and political development. Results: Among the key research findings is that history occupies a significant place in the ideology of the Russian political elite, as evidenced by its clear use during the coup led by leader Vagner Yevgeny Bryugozhin. Geopolitical factors are considered the most prominent in influencing Russian foreign and domestic policy, including the phenomenon of political coups. The research also concludes that political elite and socio-economic conflicts play an influential role in fueling political coups. Conclusions: Coups are a part of the history of violent political behavior in Russian history, serving at times as a means for the political system to renew itself and regain power. However, they are also indicators of either radical or minor changes that the system undergoes after a political coup.